ANALISIS BUTIR SOAL PENDIDIKAN AGAMA ISLAM DI SMK N 1 SEDAYU TAHUN AJARAN 2017/2018 - Anida Rahmaini; Aditya Nur Taufiq (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2018)
This research is an evaluative research that is needed to know the size of the difficulty level, the different capacity and the distractor function in the final exam of the semester the double choice of subjects of Islamic Education and Human Being in the one semester of the academic year 2017-2018. Objects studied were 30 items of multiple choice which made by the teacher of Islamic Education at grade XI A of Basic Vehicle teacher product then interpreted. This research is conducted with the level of suitability and differentiation and the use of distractor teacher artificial item is further interpreted into predetermined criteria. The method of data used is documentation and interview. This research used the quantitative data analysis that was interpreting. The data of the level of the difficult calculation result and differentiation of the teacher's multiple choice. The results showed that the level of conformity of the multiple choice which made by the teacher has not been proportional, as many as 21 product teachers problem that is not appropriate between the cognitive domains set by the teacher with the real cognitive realm according to Bloom's taxonomy. The difference level of the teacher's multiple choice was still low. A total of 21 problems of teacher have not been able to distinguish the ability between smart learners and less intelligent learners. Researchers used Microsoft excel program to get the problem. Based on results of the analysis conducted in terms of difficulty level, 30 items that included difficult items (2%), 7 items (23.3%) categories, and 27 (70%) easy category effects. In terms of distinguishing power, from 30 items that are classified as not good there are 15 (50%), enough 3 grains (10%), either 12 grains (40%), and 1 item (0%), and in terms of effectiveness of distractor use, poorly functioning item 15 items (50%), poor function 6 item (20%), function there are 9 grains (30%), and no item is good and very good Problem of Final Semester Examination of Teacher of Islamic Education and Character Program of Light Vehicle Engineering Expertise at grade XI A in SMK Negeri 1 Sedayu for Academic Year 2017/2018 including the less / not quality.